1998
DOI: 10.1080/j.1600-0412.1998.771009.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged catheterization after vaginal prolapse surgery

Abstract: Domestic use of a transurethral Foley catheter is a valid alternative to intermittent or suprapubic catheterization when normal micturition is not easily restored after vaginal prolapse surgery. It is, however, experienced as relatively unpleasant by more than one third of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…Furthermore, the practice of indwelling catheter use may be more convenient for providers who care for these patients 5 . On the contrary, prolonged catheterization increases the chance of urinary tract infection; prevents early ambulation, prolongs hospital stay and also adversely impacts post operative wellbeing 6–8 . However there is no consensus on how best to minimize complications of prolonged catheterization and practice varies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the practice of indwelling catheter use may be more convenient for providers who care for these patients 5 . On the contrary, prolonged catheterization increases the chance of urinary tract infection; prevents early ambulation, prolongs hospital stay and also adversely impacts post operative wellbeing 6–8 . However there is no consensus on how best to minimize complications of prolonged catheterization and practice varies.…”
Section: Introductionmentioning
confidence: 99%
“…In our routine practice, the actual proportion of patients requiring prolongation of catheterisation remains unknown. Moreover, bladder catheterisation increases the occurrence of urinary tract infections 1,2 and is likely to have a negative impact on the wellbeing of patients after surgery and to prolong hospital stay 3 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bladder catheterization increases the occurrence of urinary tract infections, and is likely to have a negative impact on the well being of patients after surgery and to prolong hospital stay. 5 Thakur et al 6 found that short term catheterization is more beneficial in term of lower incidence of urinary tract infection and febrile morbidities after vaginal prolapsed surgery. Hakvoort et al 7 concluded that disadvantages of prolong catheterization outweigh the advantages.…”
Section: Introductionmentioning
confidence: 99%